Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0195960
|View full text |Cite
|
Sign up to set email alerts
|

Sweat glucose and GLUT2 expression in atopic dermatitis: Implication for clinical manifestation and treatment

Abstract: Sweat includes active components and metabolites, which are needed to maintain skin homeostasis. Component changes in sweat derived from atopic dermatitis (AD) have been reported. To investigate the influence of sweat components on the pathogenesis of AD, we performed a multifaceted assessment, including nuclear magnetic resonance spectroscopy-based metabolomic analysis, and linked these features to clinical features of AD. Distinctive properties of AD sweat are the quite-variation in protein, anti-microbial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 30 publications
0
51
0
2
Order By: Relevance
“…Obesity, which is a high‐risk factor for the development of the hyperglycemia‐associated metabolic syndrome, is associated with the rising prevalence of allergic diseases . Recently, varying concentrations of glucose have been found in the sweat of atopic dermatitis patients . Thus, glucose seems to be a variable microenvironmental tissue factor with a potential impact on Th2 immunity.…”
Section: The Role Of Glucose For Th2 Cell Regulationmentioning
confidence: 99%
“…Obesity, which is a high‐risk factor for the development of the hyperglycemia‐associated metabolic syndrome, is associated with the rising prevalence of allergic diseases . Recently, varying concentrations of glucose have been found in the sweat of atopic dermatitis patients . Thus, glucose seems to be a variable microenvironmental tissue factor with a potential impact on Th2 immunity.…”
Section: The Role Of Glucose For Th2 Cell Regulationmentioning
confidence: 99%
“…Thus, the properties of sweat were compared between AD and healthy subjects who were induced to sweat in a sauna. Unexpectedly, findings revealed that the pH and salt concentration of sweat were equal or lower in AD than in healthy subjects . In sweat from subjects with AD, the concentration of LL‐37, an antimicrobial peptide, varied greatly among individuals .…”
Section: Itchy Dermatoses With Pathogenic Involvement Of Sweatmentioning
confidence: 97%
“…Unexpectedly, findings revealed that the pH and salt concentration of sweat were equal or lower in AD than in healthy subjects . In sweat from subjects with AD, the concentration of LL‐37, an antimicrobial peptide, varied greatly among individuals . As LL‐37 is cytotoxic, it can be imagined that sweat with high sweat concentrations of LL‐37 may promote inflammation and cause itching in subjects with AD (Figure ).…”
Section: Itchy Dermatoses With Pathogenic Involvement Of Sweatmentioning
confidence: 99%
See 2 more Smart Citations